Կարինի նահանգի հայ բնակչության, արևմտահայության, 1894-1896 թթ. կոտորածների, Մեծ եղեռնի զոհերի թվաքանակի հարցի շուրջ - Հովհաննես Զատիկյան (ՀՀ ԳԱՍ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
В статье с помощью архивной достоверной информации, свидетельствований статистиков, современных деятелей выявляется фальшивая сущность турецкой статистики, и по таблицам, составленных из расчета природного 0,7% роста, уточняется количество жертв резни 1894-1896 гг., Великого Геноцида 1915г. в штате Карин, а также-западных армян. In the article the false essence of Turkish statistics is brought to light by means of archival reliable information, witnessing of modem figures, statisticians, and in accordance with the tables provided by the natural 0,7% growth calculations the number of victims of the slaughters of 1894-1896 and the Great Genocide of 1915 of state Karin and the Western Armenians as well is refined upon.
Keywords: Պատմագրություն; Հայոց ցեղասպանություն (1915)